ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI CARBON EMISSION DISCLOSURES DI INDONESIA (Studi Empiris pada Perusahaan Manufaktur dan Jasa Transportasi yang Terdaftar di Bursa Efek Indonesia) - Muhammad Ali Ma’sum; Syaiko Rosyidi (BBM (Buletin Bisnis & Manajemen), 2018)
This study aims to prove the influence of industry type, size (company size), profitability, leverage and environmental performance on disclosure of carbon emissions in companies in Indonesia. The research population is all manufacturing companies and transportation services listed on the Indonesia Stock Exchange in 2010-2014. The sample method uses purposive sampling and obtained eight companies that fit the criteria, so that 40 observations were obtained as research samples. The data analysis technique uses multiple linear regression analysis and broad measurement of carbon emission disclosures using a checklist based on the information request sheet provided by CDP (Carbon Disclosure Project).The results of the study show that environmental size and performance have a positive effect on the disclosure of carbon emissions in manufacturing companies and transportation services in Indonesia. While the type of company, profitability and leverage have no significant effect on the disclosure of carbon emissions in manufacturing companies and transportation services in Indonesia. With adjusted R2 0.369, it indicates that there are other factors outside the model that can affect the level of carbon emissions disclosure.